A tutoring system using an emotion-focused strategy to support learners - Yusoff M.Z.M.; Du Boulay B. (2023)
Many tutoring systems have employed problem-focused strategies for helping students regulate their emotional states. This paper describes an affective tutoring system that added an emotion-focused strategy (a relaxation exercise) to a standard problemfocused strategy (programming advice and feedback) in order to help students better regulate their emotional states when learning about data structure manipulation.. The evaluation indicated that this additional strategy improved learning outcomes and was helpful in emotionally supporting students with both good and poor performance.